Green Extraction of Carotenoids from Pumpkin By-Products Using Natural Hydrophobic Deep Eutectic Solvents: Preliminary Insights - Lucia Sportiello; Emanuele Marchesi; Roberta Tolve; Fabio Favati (Molecules)
Natural hydrophobic deep eutectic solvents (NaHDESs), composed of natural components like menthol, fatty acids, and organic acids, are sustainable alternatives to conventional solvents for extracting carotenoids from agro-industrial by-products. This study assessed the performance of nine NaHDESs for extracting β-carotene from pumpkin peels, identifying DL-menthol/lactic acid (1:2) as the most effective solvent, achieving a yield of 0.823 ± 0.019 mg/mL of β-carotene, corresponding to 93.95% of the yield obtained using acetone. Optimization through Box–Behnken design (BBD) and response surface methodology (RSM) established ideal extraction conditions: a molar ratio of HBA:HBD at 1:4, a solvent-to-sample ratio of 26:1, and an extraction time of 30 min. These conditions maximized β-carotene recovery while minimizing energy consumption and process costs. Using NaHDESs facilitates the valorization of food waste, achieving extraction efficiencies of up to 25.05% of the theoretical carotenoid content in pumpkin peels. Their high performance and environmentally friendly profile underscore the potential of NaHDESs as sustainable alternatives to conventional solvents.